2012
DOI: 10.1371/journal.pone.0053110
|View full text |Cite
|
Sign up to set email alerts
|

Cloning, Expression and Characterization of a Gene from Earthworm Eisenia fetida Encoding a Blood-Clot Dissolving Protein

Abstract: A lumbrokinase gene encoding a blood-clot dissolving protein was cloned from earthworm (Eisenia fetida) by RT-PCR amplification. The gene designated as CST1 (GenBank No. AY840996) was sequence analyzed. The cDNA consists of 888 bp with an open reading frame of 729 bp, which encodes 242 amino acid residues. Multiple sequence alignments revealed that CST1 shares similarities and conserved amino acids with other reported lumbrokinases. The amino acid sequence of CST1 exhibits structural features similar to those … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(30 citation statements)
references
References 26 publications
(32 reference statements)
0
29
0
Order By: Relevance
“…[13] Some lumbrokinases exhibited a highly similar loop and specific pocket (Asn-Asp-iLe-Ala-Leu-Leu), similar to tPA and uPA. [1416] Besides, the amino acids, asp 507 , ser 532 and gly 534 in tPA, i.e. important substrate recognition sites for tPA and uPA, [1719]also existed in several lumbrokinases.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[13] Some lumbrokinases exhibited a highly similar loop and specific pocket (Asn-Asp-iLe-Ala-Leu-Leu), similar to tPA and uPA. [1416] Besides, the amino acids, asp 507 , ser 532 and gly 534 in tPA, i.e. important substrate recognition sites for tPA and uPA, [1719]also existed in several lumbrokinases.…”
Section: Resultsmentioning
confidence: 99%
“…These results were consistent with the report that the protein property of these proteases, by activating the plasminogen into plasmin, both had the activity of degrading the fibrin directly and the activity of degrading the fibrin indirectly. [14] However, the current fibrin plate method used in the potency determination of lumbrokinase only measured its direct fibrinolytic activity with its kinase activity excluding. Accordingly, the current method should be optimized to measure its total activity.…”
Section: Discussionmentioning
confidence: 99%
“…The high level of similarity in amino acid sequence among LK proteins indicates that some LK proteins have a comparatively recent common ancestor . The phylogenetic analysis also indicated that most LK genes were closely related to each other . The differences in LK protein sequences between species may be due to the diverse habitats occupied and food resources utilized by the different species of earthworm .…”
Section: Introductionmentioning
confidence: 98%
“…3 The phylogenetic analysis also indicated that most LK genes were closely related to each other. 4 The differences in LK protein sequences between species may be due to the diverse habitats occupied and food resources utilized by the different species of earthworm. 1 The LK gene used in this study was originally cloned from Eisenia fetida and was codon optimized by Hu et al 5 Currently, LK proteins are widely used as thrombolytic agent in China to treat coronary heart disease, cerebral infarction and deep vein thrombosis.…”
Section: Introductionmentioning
confidence: 99%
“…Various LK genes have been cloned and produced in different expression systems including Escherichia coli (E. coli) [ 7 , 8 ], yeast [ 9 , 10 ], and mammalian [ 11 ] systems. However, results from those investigations have not been promising.…”
Section: Introductionmentioning
confidence: 99%